Harm and offence in media content : a review of the evidence - Hargrave, Andrea Millwood (Intellect, 2006)
In today's media and communications environment, pressing questions arise regarding the media's potential for harm, especially in relation to children. This book offers a unique and comprehensive analysis of the latest research on content-related media harm and offence. For the first time, a balanced, critical account brings together findings on both established and newer interactive media. Arguing against asking simple questions about media effects, the case is made for contextualising media content and use within a multi-factor, risk-based framework in order to guide future research and policy formation.